Penetration depths with an ultrasonic mini insert compared with a conventional curette in patients with periodontitis and in periodontal maintenance - Dick S. Barendregt, Ubele van der (Blackwell Synergy, 2008)
Aim: The aim of the study was to test whether a slim Ultrasonic Tip reaches a more apical position when penetrating a periodontal pocket compared with the working blade of a conventional Gracey Curette in both untreated periodontitis and periodontal maintenance patients. Material and Methods: Twenty untreated and 15 periodontal maintenance patients were selected based on the presence of at least one site a pocket of X5mm in each quadrant. Recordings were made at the four approximal sites of four experimental teeth in each patient. First, the probing pocket depth was measured with the Jonker Probes. Second in randomized order, the penetration depth was assessed with an EMS PS Ultrasonic Tip and a Gracey Curette. Results: In the periodontitis group, the Ultrasonic Tip penetrated significantly deeper than the Jonker Probe and the Gracey Curette. In the maintenance group, no differences were observed. Comparing the penetration of the instruments between groups, as related to the Jonker Probe measurements, only in the periodontitis group did the Ultrasonic Tip reach a significantly more apical level. Conclusion: The results of the present study show that in untreated periodontitis patients, the Ultrasonic Tip penetrated the pocket deeper than the pressure-controlled probe and the Gracey Curette.